تقصي الدور الوقائي للمستخلص المائي لأوراق نبات الزعتر على السمية الكبدية المستحدثة بعقار ديكلوفيناك الصوديوم في الهامستر السوري - داود, علي; دباغ, مروان; سلمان, حلا (Latakia University Journal -Biological Sciences Series, 2019)
هدفت الدراسة الحالية إلى تقصي تأثير المستخلص المائي لأوراق نبات الزعتر البري على السمية الكبدية المستحدثة بعقار ديكلوفيناك الصوديوم في الهامستر السوري. شملت الدراسة 32 حيوان وزعت في أربع مجموعات متساوية: المجموعة الأولى (شاهدة)، والمجموعة الثانية جُرعت فقط بمستخلص أوراق الزعتر (300 ملغ/كغ من وزن الجسم) مرة واحدة يومياً لمدة خمس أسابيع، وجرعت المجموعة الثالثة بعقار ديكلوفيناك الصوديوم (6 ملغ/كغ) ثلاث مرات اسبوعياً لمدة خمس أسابيع ، في حين جرعت المجموعة الرابعة بشكل متزامن بكل من مستخلص أوراق الزعتر وديكلوفيناك الصوديوم بنفس الطريقة والجرعات السابقة ولنفس المدة الزمنية. أظهرت نتائج الدراسة الحيوية الكيميائية ارتفاعاً معنوياً في تراكيز أنزيميALT، وAST(p<0.001)، والبولة، وحمض البول، والكرياتنين (p<0.001)، في حين سُجل انخفاض معنوي (p< 0.001) في تركيز الألبومين في مصل دم حيوانات المجموعة الثالثة مقارنة مع المجموعة الشاهدة، والمجموعة الثانية. إضافة لذلك، سُجل انخفاض معنوي في تراكيز جميع هذه المعايير ( 0.001>P ) وارتفاع معنوي في ألبومين مصل دم حيوانات المجموعة الرابعة بفعل التجريع المتزامن للمستخلص المائي لأوراق الزعتر مع ديكلوفيناك الصوديوم مقارنة مع مثيلاتها في مصل دم المجموعة الثالثة. من جانب آخر، بينت نتائج الدراسة النسيجية لأكباد حيوانات المجموعة الثالثة ظهور علامات واضحة لتنخر خلوي تجلت بانتباج خلايا الكبد وضعف تلونها، وفقدان أنوية بعضها، وتحطم أغشيتها الخلوية، وحدوث ارتشاح التهابي شديد للعدلات واللمفاويات. كما لوحظ احتقان وعائي في الأوردة المركزية والبابية للكبد وتوسع في الجيوب الوريدية. وقد استعادت أنسجة الكبد جزءاً مهماً من عافيتها وسجل تنشيط لانقسام خلايا الكبد في الحيوانات التي جُرعت بمستخلص الزعتر بالتزامن مع ديكلوفيناك الصوديوم. يتضح من نتائج الدراسة الحالية أن المستخلص المائي لأوراق نبات الزعتر يشكل منتج عشبي طبيعي فعال ضد السمية الكبدية والإجهاد التأكسدي المُحدث بديكلوفيناك الصوديوم. The present study aimed to evaluate the protective effect of aqueous extract of thymus leafs against diclofenac sodium- induced hepatotoxicity in male Syrian hamster. Thirty-two mal hamsters were used and equally divided into four groups. Group 1 is as control, while group 2 received orally a dose of thymus extract (300 mg/kg.b.w) daily for five weeks. Groups 3 received diclofenac sodium (6mg/kg.b.w) three times/week also for five weeks, and Groups 4 received a dose of diclofenac sodium in combination with a dose of thymus extract in the same way and concentrations. At the end of the experiment, blood was taken from each animal and stored until biochemical study. Then, hamsters were scarified, they were autopsied, and liver tissue samples were prepared for histopathology assessment. Biochemical study showed a significant increase in the levels of ALT, AST enzymes, Creatinine, uric acid, and urea (p<0.001) while albumin level was decreased (p<0.001) in blood serum of groups 3 compared to control and second groups. Also, a significant decreasing in the level of all the precedent biochemical parameters (p<0.001) and elevation of albumin has been recorded in blood serum of 4th group. In addition, histopathological study of liver tissue revealed strong indices of injury mediated by diclofenac sodium especially congestion of liver cells, dilation of hepatic portal and central veins, cell nucleus disappearance, a as well as inflammatory cells infiltration. These indices were greatly ameliorated and activation of liver cells division was recorded in liver of animals of 4th group. The results of the present study show that the water extract of thyme leaves is an effective natural herbal product against hepatotoxicity and oxidative stress induced by sodium diclofenac.